Taxonomic characterization of Paradoxical frogs (Anura, Hylidae, Pseudae): geographic distribution, external morphology, and morphometry - Garda, Adrian Antonio; Santana, Diego José; de Avelar São-Pedro, Vinícius (Zootaxa, 2010)
Paradoxical frogs (Pseudae) have been difficult to characterize morphologically, and their phylogenetic affinities have long remained elusive despite several taxonomic revisions of the group. Based on the analysis of 1388 specimens we evaluate morphological characters used to identify and group species throughout their distributions. We also suggest other, previously unreported phylogenetically informative morphological characters and evaluate morphometric differences among species. The geographic distribution of Pseudae in Brazil confirms, to a certain degree, their association with hydrographic basins. Geographic variation in morphology is extensive in some species. Some characters traditionally used to identify species (e.g. stripes on the ventral surface of the thigh) vary extensively among populations, and in most cases do not distinguish among species. Body shape differences, skin texture, size and number of carpal and metatarsal tubercles, supernumerary tubercles, vocal sac structure, dorsal coloration, ventral stripes on the thigh, and geographic distribution need to be considered together to correctly identify species. Size of reproductive Pseudis varies considerably, most likely as a response to local conditions altering larval size at metamorphosis, given that postmetamorphic growth is reduced or absent in Pseudis. The previously suggested suite of ecological characters that allow disproportionate larval growth are therefore substantiated, while the paradox of a conserved body plan coupled with extensive character variation is implicated as the cause for confusion in the taxonomy of paradoxical frogs.